Pengaruh Perlakuan Jenis Pelarut dan Rasio Bahan terhadap Karakteristik Mutu Pati Ubi Gadung (Dioscorea hispida Dennst) - Septianto Billy, Dwiyan Ricard; Hartiati, Amna; Admadi, Bambang (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2020)
This study aims to determine the effect of various preliminary treatments on the quality characteristics of ubi gadung’s starch (Dioscorea hispida dennst) and to find out the preliminary treatment that can produce ubi gadung starch with the best quality. This study used a randomized block design (RBD) with four preliminary treatments including water immersion, 10% NaCl, 15% NaCl and 0.3% Na Metabisulfite, which were repeated twice. The parameters tested were water content, starch content, yield and sensory including plural color comparisons. Data were analyzed using ANOVA and continued with Duncan's (? = 0.5%). The results showed that each preliminary treatment had no significant effect on each parameter observed, and the best results were in the 15% NaCl immersion treatment. The 15% NaCl immersion method produces starch with a moisture content of 8.50%, starch content of 14.35%, yield of 12.52%, and multiple color comparison test at score 5 with the most frequency (closest to R = 4) Keywords : wild root yam, immersion, starch